Further Refinements of Certain Pachpatte-Gamidov-Type Inequalities in Two Independent Variables and their Applications. Issue 1 (2nd January 2021) - Boukerrioua, Khaled; Ayari, Amira
Abstract: The main objective in this paper is to investigate some Pachpatte- Gamidov-type inequalities in two independent variables. The obtained inequalities can be used as handy tools to study the properties of certain differential and integral equations.